2013
DOI: 10.1371/journal.pone.0081769
|View full text |Cite
|
Sign up to set email alerts
|

WNT3 Inhibits Cerebellar Granule Neuron Progenitor Proliferation and Medulloblastoma Formation via MAPK Activation

Abstract: During normal cerebellar development, the remarkable expansion of granule cell progenitors (GCPs) generates a population of granule neurons that outnumbers the total neuronal population of the cerebral cortex, and provides a model for identifying signaling pathways that may be defective in medulloblastoma. While many studies focus on identifying pathways that promote growth of GCPs, a critical unanswered question concerns the identification of signaling pathways that block mitogenic stimulation and induce earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 102 publications
2
54
1
1
Order By: Relevance
“…The lack of an internal cell division clock (Espinosa and Luo, 2008) has focussed attention on cell non-autonomous factors such Wnt and bone morphogenetic protein (BMP) pathway signals in the EGL. For example, non-canonical Wnt signalling via Wnt3 has recently been shown to be capable of decreasing proliferation independently of BMP signalling (Anne et al, 2013). Conversely, multiple BMPs are expressed in the cerebellum during EGL development and can antagonise the Shh-dependent proliferation of granule progenitors both in vitro and in slice cultures (Rios et al, 2004) through regulation of Atoh1 (Zhao et al, 2008) and via miR22 (Berenguer et al, 2013).…”
Section: Balancing Proliferation and Differentiation In The External mentioning
confidence: 99%
“…The lack of an internal cell division clock (Espinosa and Luo, 2008) has focussed attention on cell non-autonomous factors such Wnt and bone morphogenetic protein (BMP) pathway signals in the EGL. For example, non-canonical Wnt signalling via Wnt3 has recently been shown to be capable of decreasing proliferation independently of BMP signalling (Anne et al, 2013). Conversely, multiple BMPs are expressed in the cerebellum during EGL development and can antagonise the Shh-dependent proliferation of granule progenitors both in vitro and in slice cultures (Rios et al, 2004) through regulation of Atoh1 (Zhao et al, 2008) and via miR22 (Berenguer et al, 2013).…”
Section: Balancing Proliferation and Differentiation In The External mentioning
confidence: 99%
“…S2F-G) confirms their localization to a proliferation niche. The role of Wnt3 in inhibiting proliferation of cultured cerebellar granule progenitors and regulating its neurogenesis has been documented in mice (Anne et al, 2013). We investigated whether a similar role exists for Wnt3 by assessing its impact on cerebellum neurogenesis in zebrafish.…”
Section: F2mentioning
confidence: 99%
“…Cerebellar vermis hypoplasia in Joubert syndrome, for example, is linked to defective canonical Wnt signaling (Lancaster et al, 2011). Wnt3 is expressed in the developing cerebellum and the dorsal spinal cord of all vertebrates (Roelink and Nusse, 1991;Bulfone et al, 1993;Garriock et al, 2007;Clements et al, 2009;Anne et al, 2013). In mice, Wnt3 is expressed prior to gastrulation and its targeted deletion causes an early developmental arrest (Liu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is accepted that transactivation of LH receptor is downstream of PKC cascade (Leserer et al 2000, Cattaneo et al 2014; it is also suggested that PKC can act downstream to EGF and that EGF-like growth factors can activate PKC directly (Li et al 1991, Anne et al 2013, Liu et al 2014. To determine whether inhibition of PKC will hamper the ability of AREG to downregulate PEDF expression, we followed the expression of PEDF in AREG-stimulated LH-15 cells with or without pretreatment with a PKC inhibitor (GF; 10 mM).…”
Section: Pedf Regulation In Granulosa Cellsmentioning
confidence: 99%